2020
DOI: 10.1542/peds.2019-3773
|View full text |Cite
|
Sign up to set email alerts
|

Electromagnetic Versus Blind Guidance of a Postpyloric Feeding Tube in Critically Ill Children

Abstract: BACKGROUND AND OBJECTIVES: Postpyloric feeding tube placement is a time-consuming procedure associated with multiple attempts and radiation exposure. Our objective with this study is to compare the time, attempts, and radiation exposure using the electromagnetic versus blind method to place a postpyloric feeding tube in critically ill children. Our hypothesis is that using electromagnetic guidance decreases the procedure time, number of x-rays, and number of attempts, compared to the blind method.METHODS: Elev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Although X-ray examination is used to determine the tube position, children and pregnant women may face the risk of radiation overexposure ( 17 ). It has been reported that the use of magnetic navigation ( 18 ) and B-ultrasound assistance ( 19 ) can improve the success rates of blind intubation, but the two techniques require more manpower and material resources, and require expensive equipment and long-term experiences.…”
Section: Introductionmentioning
confidence: 99%
“…Although X-ray examination is used to determine the tube position, children and pregnant women may face the risk of radiation overexposure ( 17 ). It has been reported that the use of magnetic navigation ( 18 ) and B-ultrasound assistance ( 19 ) can improve the success rates of blind intubation, but the two techniques require more manpower and material resources, and require expensive equipment and long-term experiences.…”
Section: Introductionmentioning
confidence: 99%
“…The study verified a success rate of 96.4% for the electromagnetic technique and 66.7% for the conventional technique. Regarding time, electromagnetic insertion had an average duration of 2.5 minutes, while "blindly", 19 minutes, in addition, the electromagnetic method presented a reduced need to confirm the positioning by radiography examination 44 .…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have therefore focused on efficient and timely placement of postpyloric tubes [35][36][37]. Success rates in postpyloric tube placement on firsttime attempt using blind-bedside placement, electromagnetic-guidance and pH guided devices vary, with some studies reporting success rates of greater than 80% with any one of these techniques [38][39][40]. Point-of-care ultrasound has now also been utilized for postpyloric tube placement with an 87-94% success rate in critically ill children, making ultrasound a promising tool for timely postpyloric tube placement [41,42].…”
Section: Gastrointestinal Dysfunction: Diagnosis and Alternative Ente...mentioning
confidence: 99%